Relevansi Visi, Misi, Tujuan dan Kurikulum Sekolah Inklusif - Hasbiyallah Hasbiyallah; Rifa Nailufar; Rizki Nur Amaliah (JUMPA : Jurnal Manajemen Pendidikan, 2022)
Inclusive education isi ai manifestationi ofi thei idealsi ofi thei Indonesiani nationi to provide equitable and equitable education. The school exists as an institution that is directly engaged in managing the educational and learning process for the community. It is necessary to have the relevance ofi thei visioni, missioni, goalsi andi curriculumi in schools, so thati these idealsi are realized. This research will discuss the relevance between thei visioni, missioni, goalsi andi curriculumi in schoolsi as an efforti toi achieve goals. What is the foundation for making a vision for inclusive schools? How isi thei visioni andi missioni ofi inclusive schools related? Whati is the purpose of inclusive schools? And how do these three factors affect the curriculum thati isi carriedi outi in schoolsi? This study seeks to review these points and their implementation at SMP Al-Biruni Cerdas Mulia which is a leading inclusive school ini thei cityi ofi Bandungi. Thisi studyi used qualitativei descriptive analysis. This study seeks to review these pointsi and their implementation at SMP Al-Biruni Cerdas Mulia which is a leading inclusive school ini thei cityi ofi Bandungi. This studyi usedi qualitativei descriptive analysis. Thei technique of collecting data through a structured cloud was carried out to the principali of SMP Al-Biruni Cerdas Mulia.